Identification of immunogenic proteins of Waddlia chondrophila. - Carole Kebbi-Beghdadi (Public Library of Science (PLoS), 2012)
Evidence is growing for a role of Waddlia chondrophila as an agent of adverse pregnancy outcomes in both humans and ruminants. This emerging pathogen, member of the order Chlamydiales, is also implicated in bronchiolitis and lower respiratory tract infections. Until now, the serological diagnosis of W. chondrophila infection has mainly relied on manually intensive tests including micro-immunofluorescence and Western blotting. Thus, there is an urgent need to establish reliable high throughput serological assays. Using a combined genomic and proteomic approach, we detected 57 immunogenic proteins of W. chondrophila, of which 17 were analysed by mass spectrometry. Two novel hypothetical proteins, Wim3 and Wim4, were expressed as recombinant proteins in Escherichia coli, purified and used as antigens in an ELISA test. Both proteins were recognized by sera of rabbits immunized with W. chondrophila as well as by human W. chondrophila positive sera but not by rabbit pre-immune sera nor human W. chondrophila negative sera. These results demonstrated that the approach chosen is suitable to identify immunogenic proteins that can be used to develop a serological test. This latter will be a valuable tool to further clarify the pathogenic potential of W. chondrophila.